MEMS piezoresistive accelerometer sensor for gait analysis - Siti Nurdiyana Abd. Rashid (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The main purpose of this research is to design and develop a MEMS piezoresistive accelerometer sensor for gait analysis. Specific objectives of this project are listed as below ; to design piezoresistive accelerometer sensor using COMSOL Multiphysics software ; to make a comparison between each design that has different length of beams ; to determine the maximum and minimum measurement of applied acceleration that the sensor can detect or produce.